Surface Water Quality Assessment of Tunggak River Gebeng, Pahang, Malaysia - Hossain, Mohamed Amjed (2013)
The objective of the study was to assess the water quality of Tunggak River and to find out the impact of industries on it. Water quality parameters were analyzed collecting samples from 8 stations during February-July 2012 across the river basin to fulfill the objective. Temperature, pH, DO, turbidity, TDS, EC and salinity data were collected using YSI during sampling. The physico-chemical parameters were analyzed using APHA & HACH standard methods. Heavy metals were determined using ICP-MS spectrometry. SPSS 16.0 statistical software was used for data analysis. The result showed that, average temperature and DO concentration was recorded 31.300C and 2.24mg/L respectively; while the pH was found acidic at upper stream and alkaline at mid-stream region. The ranges of turbidity and TDS was observed 4.55 to 28.75 NTU and 19.6 to 49400mg/L respectively. NH4-N was recorded higher with a mean value of 1.96 mg/L. Average concentration of SO4 and PO43- was observed 193.26 and 1.71 mg/L respectively. Concentration of BOD and COD were found higher at all parts of the river with an average value of 22.04 and 51.16 mg/L respectively. Regarding heavy metals, Pb, Hg, and Co was recorded in toxic level in the surface water of the river.